Carbonization of Lignin Extracted from Liquid Waste of Coconut Coir Delignification - Widiyastuti Widiyastuti; Mahardika Fahrudin Rois; Heru Setyawan; Siti Machmudah; Diky Anggoro (Indonesian Journal of Chemistry, 2020)
Lignin as a by-product of the pulping process is less widely used for worth materials. In this study, the utilization of lignin by-product of the soda delignification process of coconut coir converted to the activated carbon by a simple precipitation method followed by the carbonization at various temperatures is presented. The by-product liquor of the soda delignification process having a pH of 13.4 was neutralized by dropping of hydrochloric acid solution to achieve the pH solution of 4 resulting in the lignin precipitation. The precipitated was washed, filtered, and dried. The dried lignin was then carbonized under a nitrogen atmosphere at various temperatures of 500, 700, and 900 °C. The dried lignin and carbonized samples were characterized using SEM, XRD, FTIR, and nitrogen adsorption-desorption analyzer, to examine their morphology, X-Ray diffraction pattern, chemical bonding interaction, and surface area-pore size distribution, respectively. The characterization results showed that the functional groups of lignin mostly disappeared gradually with the increase of temperature approached the graphite spectrum. The XRD patterns confirmed that the carbonized lignin particles were amorphous and assigned as graphitic. All samples had a pore size of 3–4 nm classified as mesoporous particles. This study has shown that the carbonization lignin at a temperature of 700 °C had the highest surface area (i.e. 642.5 m2/g) in which corresponds to the highest specific capacitance (i.e. 28.84 F/g).